Clinical pharmacists’ education on nutritional supplements for community-based stunting prevention - A. Wardah Muzfah; Trimaya Cahya Mulat; Darmi Arda; Maria Kurni Menga (Jurnal Pengabdian Masyarakat Edukasi Indonesia, 2026)
Stunting remains a significant public health issue in Indonesia, closely linked to chronic undernutrition and micronutrient deficiencies during the first 1,000 days of life. Limited community knowledge regarding the rational use of nutritional supplements and micronutrients contributes to inappropriate practices that reduce the effectiveness of stunting prevention programs. This community service program aimed to improve community knowledge and awareness of appropriate nutritional supplement use through pharmacist-led education. The program was conducted using a structured, participatory approach consisting of situational analysis, educational material development, community education implementation, monitoring and evaluation, and follow-up activities. Clinical pharmacists delivered educational sessions through interactive lectures and discussions involving mothers, caregivers, and community health volunteers. Program evaluation was conducted using pre- and post-education assessments to measure changes in knowledge related to the roles of micronutrients, correct dosage and administration, safety considerations, and the complementary role of supplements in balanced nutrition. The results showed a clear improvement in participants’ knowledge across all assessed indicators following the intervention. Participants demonstrated a better understanding of the importance of micronutrients for child growth, appropriate supplement use, and safety aspects, as well as increased awareness that supplements should support, rather than replace, balanced diets. These findings suggest that pharmacist-led community education is an effective strategy for strengthening stunting prevention efforts through the rational use of nutritional supplements.